Implementation of Merdeka Curriculum: In Lesson Study Based Differentiated Learning - Sri Rejeki; Rihal Jayadi; Wahyu Azwar (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to conduct a meta-analysis of various studies discussing the implementation of the Independent Curriculum (Kurikulum Merdeka) in differentiated learning based on the lesson study approach across different educational levels. Methodology: The study employs a quantitative meta-analysis method by analyzing 88 articles published between 2020 and 2025, retrieved from several academic databases such as Google Scholar, ScienceDirect, DOAJ, PubMed, WorldCat, Dimensions, and Portal Garuda. Main Findings: The findings show a very high overall effect size (ES = 1.086; SE = 0.157). Specifically, elementary (ES = 1.049) and senior high schools (ES = 0.826) show high effects, while junior high schools demonstrate the strongest and most consistent impact (ES = 1.475). Novelty/Originality of this study: This study’s novelty lies in integrating differentiated learning with the lesson study approach under the Independent Curriculum, offering empirical evidence of its strong positive effect on learning quality across educational levels and highlighting its potential as an innovative model for improving teaching effectiveness in Indonesian schools.